대학생의 채소 섭취 행동변화단계에 따른 채소 섭취 관련 인식, 자아효능감 및 식행동 - 안윤(Yun Ahn); 김경원(Kyung Won Kim) (Korean journal of community nutrition, 2012)
The purpose of this study was to examine beliefs, self-efficacy and eating behaviors by the stages of change in vegetable consumption among college students (n = 297). A survey was conducted to examine study variables, and subjects were categorized into three groups based on the stages of change: precontemplation/contemplation stage (PC/C), preparation stage (P), action/maintenance stage (A/M). Subjects had 3.7 servings of vegetables a day, and vegetable consumption was significantly different by stages of change (p < 0.001). The A/M group showed higher score on beliefs regarding vegetable consumption (p < 0.001) than the other groups, and perceived benefits of vegetable consumption (e.g. cancer prevention) more strongly (p < 0.05). The PC/C group felt more barriers than the A/M group, such as disliking cooking methods, texture of vegetables (p < 0.001), bad taste and bad experience of eating vegetables (p < 0.05). Self-efficacy score was 27.2, with decreasing self-efficacy from A/M to P, PC/C (p < 0.001). The A/M group showed more confidence in nine behaviors such as "eating vegetables during meals" and "replacing menu at home with more vegetable dishes" (p < 0.001) than the other groups. The A/M group had more desirable eating behaviors (e.g, having a variety of foods, eating regularly, consumption of food groups). This study suggests that target population for education and educational strategies be different based on the stages of change. For those in the PC/C stage, education might focus on reducing barriers and increasing self-efficacy. For those in the A/M stage, it is necessary to use strategies to maintain and reinforce behaviors for enough vegetable consumption.